Scope of Introduction to Children's Social Sciences Seen from the AUD Social Skills Aspect - Susanti, Apsari; Musafir, Musafir; Irnawati, Ema; Handriyanti, Handriyanti; Saofiya, Saofiya; Upriani, Upriani (Jurnal Ilmiah Mandala Education (JIME), 2025)
Early childhood is a golden age, therefore this period is important to support the social aspects of early childhood so that children can collaborate and establish good relationships and communication with people around them or social groups. This article discusses the scope that can support the social development of early childhood optimally. This article aims to understand the social development of early childhood. The method used is literature study, referring to various relevant literature sources.  The results of analysis from various scientific literature show that the introduction of social sciences in early childhood is very important to support their social development. Children in this phase, known as the golden age, need to be equipped with social skills so they can interact and adapt well in social environments. Several studies have identified various factors that influence social development as well as the scope of its introduction, namely parents, the environment, and interactions with peers.